Words and Deeds - Eersels, Ben; Haemers, Jelle (Brepols, 2020)
This book focuses on the city and urban politics, because historically towns have been an interesting laboratory for the creation and development of political ideas and practices, as they are also today. The contributions in this volume shed light on why, how and when citizens participated in the urban political process in late medieval Europe (<span class=